An Emotional Response to the Value of Visualization - Wang, Yun; Segal, Adrien; Klatzky, Roberta; Keefe, Daniel F.; Isenberg, Petra; Hurtienne, Jorn; Hornecker, Eva; Dwyer, Tim; Barrass, Stephen; Rhyne, Theresa-Marie (IEEE computer graphics and applications, 2019)
When assessing the value of visualizations, researchers traditionally focus on efficiency, comprehension, or insight. However, analyzing successful data physicalizations leads to a deep appreciation for hedonic qualities. Informed by the role of emotion in psychology, art, design, marketing, and HCI, we argue for an expanded definition of value, applicable to all forms of data visualization.